Implementation and Quality of Corporate Water Reporting Based on GRI 303:2018: A Scoping Review - Ratri Nur Alfianti (Jurnal Riset Akuntansi dan Auditing, 2026)
Abstract - Global water scarcity and climate change urgently demand substantive corporate transparency in water management, yet the extent to which GRI 303:2018 has advanced this goal remains insufficiently mapped in the literature. This study aims to (1) map corporate water reporting patterns, (2) identify implementation challenges, and (3) examine how reporting quality has been operationalized in empirical studies following GRI 303:2018 adoption, using a scoping review approach Arksey & O'Malley framework and PRISMA-ScR covering 8 studies from 2019-2025. Findings reveal a consistent pattern of information asymmetry: companies aggressively disclose water withdrawal (GRI 303-3) while minimally reporting discharge and consumption in water-stressed areas (GRI 303-4/5), consistent with symbolic compliance predicted by legitimacy theory. Key challenges include definitional ambiguity around "water stress" and non-comparable reporting formats across companies, while quality measurement in the literature remains predominantly checklist-based and unable to detect substantive versus symbolic disclosure. This study contributes a unified conceptual map across three dimensions previously studied in isolation: reporting patterns, implementation challenges, and quality operationalization. Together, these dimensions are shown to share the same legitimacy logic, thereby informing more holistic reform agendas for corporate water accountability. Abstrak - Kelangkaan air global dan perubahan iklim menuntut transparansi korporat yang substantif dalam pengelolaan air, namun sejauh mana GRI 303:2018 telah mewujudkan tujuan tersebut masih kurang terpetakan dalam literatur. Penelitian ini bertujuan (1) memetakan pola pelaporan air korporat, (2) mengidentifikasi tantangan penerapan, dan (3) menelaah bagaimana kualitas pelaporan dioperasionalisasikan dalam studi empiris pasca-adopsi GRI 303:2018, menggunakan pendekatan scoping review berkerangka Arksey & O'Malley dan pedoman PRISMA-ScR atas 8 studi tahun 2019–2025. Temuan menunjukkan pola asimetri informasi yang konsisten: perusahaan agresif mengungkapkan pengambilan air (GRI 303-3) namun minim melaporkan debit limbah dan konsumsi di wilayah stres air (GRI 303-4/5), konsisten dengan kepatuhan simbolis yang diprediksi teori legitimasi. Tantangan utama meliputi ambiguitas definisi "stres air" dan format pelaporan yang tidak terbandingkan antar perusahaan, sementara pengukuran kualitas dalam literatur masih dominan berbasis daftar periksa dan tidak mampu membedakan pengungkapan substantif dari yang bersifat simbolis. Penelitian ini berkontribusi dengan menyediakan peta konseptual terpadu atas tiga dimensi yang sebelumnya diteliti secara terpisah, yakni pola pelaporan, tantangan implementasi, dan operasionalisasi kualitas, yang menunjukkan bahwa ketiganya berakar pada logika legitimasi yang sama, sehingga menginformasikan agenda reformasi akuntabilitas air korporat yang lebih holistik.